2013
DOI: 10.1007/s00381-013-2185-6
|View full text |Cite
|
Sign up to set email alerts
|

Rapamycin has a beneficial effect on controlling epilepsy in children with tuberous sclerosis complex: results of 7 children from a cohort of 86

Abstract: This is the first study that showed that rapamycin is an effective agent for controlling epilepsy without any significant side effect in children with TSC. Rapamycin seems to be effective after 6 months of therapy, and we recommend tapering the dosage after successful management of epilepsy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(24 citation statements)
references
References 70 publications
0
24
0
Order By: Relevance
“…Even if we used the lower rapamycin dose, the growth-retarding effects were evident. In more severe epilepsies such as those associated with TSC, rapamycin can still be a useful drug, since its beneficial effects may outweigh the negative side effects; clinical trials appear successful [37][38][39] and recently, it was found that intermittent dosing of rapamycin is effective, while limiting the side effects in a mouse model of TSC. 23 Recently we also reported a significant reduction in brain growth after 6-week rapamycin treatment in KA-treated rats.…”
Section: Discussionmentioning
confidence: 99%
“…Even if we used the lower rapamycin dose, the growth-retarding effects were evident. In more severe epilepsies such as those associated with TSC, rapamycin can still be a useful drug, since its beneficial effects may outweigh the negative side effects; clinical trials appear successful [37][38][39] and recently, it was found that intermittent dosing of rapamycin is effective, while limiting the side effects in a mouse model of TSC. 23 Recently we also reported a significant reduction in brain growth after 6-week rapamycin treatment in KA-treated rats.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have indicated that mTOR plays a role in the epileptogenic process in TS inasmuch as early treatment with the mTOR inhibitor rapamycin can prevent the development of epilepsy in mice with conditional inactivation of the Tsc1 gene [114]. A retrospective clinical study confirmed the potential utility of rapamycin for the treatment of seizures in children with TSC; whether this action is disease-modifying remains to be determined [115]. Interestingly, mTOR dysregulation has been demonstrated in a variety of other types of epilepsy, including epilepsies associated with brain injury, SE, genetic mutations, brain tumors, and focal cortical dysplasias [116].…”
Section: The Mammalian Target Of Rapamycin Pathwaymentioning
confidence: 98%
“…In another study in which 7 patients with tuberous sclerosis complex who received everolimus or sirolimus treatment were examined, it was reported that mTOR inhibitors were efficient in resistant epilepsy (41). In a study performed in our country, it was reported that rapamycine was given to 7 of 86 patients with a diagnosis of tuberous sclerosis complex with different reasons, 5 of these patients had resistant seizures and all patients were free of seizure after a 6-month treatment period (42). Sirolimus treatment was given to 45% of the patients becasue of SEGA or angiomyolipomas.…”
Section: B Clinical Diagnostic Criteriamentioning
confidence: 99%